The Role of Positive and Negative Emotions in Shaping Willingness to Communicate in a Second Language: Self-Perceived Communication Competence as a Moderator - Muhammad Umar Nadeem; Muhammad Adnan; Anastassia Zabrodskaja (MDPI AG, 2023)
Willingness to communicate (WTC) in a second language (L2) is one of the key concepts in L2 communication and learning. Previously, research practice in this area has been more concerned with investigating the relationship between individual negative emotions and WTC. However, insufficient attention has been given to a wide range of positive and negative emotions contributing to WTC. This study aims to address the impact of emotions (positive and negative) and self-perceived communication competence (SPCC) on WTC in an L2 in the context of Pakistan. The broaden-and-build theory of positive emotions has driven theoretical reasoning. Higher education students (N = 401) were considered the participants of this study and were approached conveniently. Data were processed and analyzed in SPSS. The findings revealed that positive emotions and SPCC positively influence WTC in an L2. On the contrary, negative emotions have a negative impact on WTC in an L2. Additionally, SPCC appears to be a significant moderator in the relationship between emotions (positive and negative) and WTC in an L2. The study's findings have important practical implications for Pakistan's Higher Education Commission (HEC) in drafting and implementing policies to enhance students' WTC within higher education classrooms.